Why Current Doppler Ultrasound Methodology Is Inaccurate in Assessing Cerebral Venous Return: The Alternative of the Ultrasonic Jugular Venous Pulse - Paolo Zamboni (Behavioural Neurology)
Assessment of cerebral venous return is growing interest for potential application in clinical practice. Doppler ultrasound (DUS) was used as a screening tool. However, three meta-analyses of qualitative DUS protocol demonstrate a big heterogeneity among studies. In an attempt to improve accuracy, several authors alternatively measured the flow rate, based on the product of the time average velocity with the cross-sectional area (CSA). However, also the quantification protocols lacked of the necessary accuracy. The reasons are as follows: (a) automatic measurement of the CSA assimilates the jugular to a circle, while it is elliptical; (b) the use of just a single CSA value in a pulsatile vessel is inaccurate; (c) time average velocity assessment can be applied only in laminar flow. Finally, the tutorial describes alternative ultrasound calculation of flow based on the Womersley method, which takes into account the variation of the jugular CSA overtime. In the near future, it will be possible to synchronize the electrocardiogram with the brain inflow (carotid distension wave) and with the outflow (jugular venous pulse) in order to nicely have a noninvasive ultrasound picture of the brain-heart axis. US jugular venous pulse may have potential use in neurovascular, neurocognitive, neurosensorial, and neurodegenerative disorders.